Increased serum osteoprotegerin in disorders characterized by persistent immune activation or glucocorticoid excess--possible role in bone homeostasis - Ueland, T; Bollerslev, J; Godang, K; Muller, F; Froland, SS; Aukrust, P (European journal of endocrinology, 2001)
OBJECTIVE: To investigate the possible role of osteoprotegerin (OPG) in bone metabolism in humans by measuring serum levels of OPG in five well-characterized patient populations with known or suspected pathology in bone homeostasis, but with differences in the pathogenesis of these disturbances. DESIGN: The study comprised 34 patients with Cushing's syndrome (CS), 24 acromegalic patients, 16 patients with growth hormone deficiency (GHD), 29 HIV-infected patients, 25 patients with common variable immunodeficiency (CVI) and 59 age- and sex-matched healthy controls (CTR). METHODS: Serum levels of tumor necrosis factor (TNF)-alpha, OPG, C-terminal telopeptides of Type-I collagen (CTX-I) and osteocalcin were determined in all study subjects as well as cortisol (CS and CTR) and IGF-I (acromegaly, GHD and CTR). RESULTS: OPG levels were significantly elevated in both CVI (median increase approximately 32%, P < 0.05) and HIV-infected patients with especially high levels in the latter group ( approximately 52%, P < 0.001), significantly correlated with increased TNFalpha levels (r = 0.47, P < 0.02). Also CS patients had elevated serum OPG ( approximately 24%, P < 0.01), significantly correlated with increased serum cortisol (r = 0.35, P < 0.05). In contrast, OPG levels in acromegalic and GHD patients were not different from healthy controls. No relationships were found between OPG levels and CTX-I or osteocalcin. CONCLUSIONS: These findings suggest that enhanced OPG levels may be a compensatory response to enhanced osteoclast activity or negative bone remodeling balance in some conditions, but may also be a parameter of enhanced activity in the OPG system possibly correlated to enhanced activity of other members of the TNF family.